Hydrogenated styrene-conjugated diene copolymer, foam material thereof and use thereof

JP7640508B2Active Publication Date: 2025-03-05CHINA PETROLEUM & CHEMICAL CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2022164820
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-10-30
Filing Date
2022-10-13
Publication Date
2025-03-05
Estimated Expiration
2039-10-29

Smart Images

  • Figure 0007640508000012
    Figure 0007640508000012
  • Figure 0007640508000013
    Figure 0007640508000013
  • Figure 0007640508000014
    Figure 0007640508000014
Patent Text Reader

Abstract

Provided are a hydrogenated styrene-conjugated diene copolymer that can achieve high resilience and low compression deformation without employing a chemical foaming process, a foam material obtained from the copolymer, and uses thereof. [Solution] The copolymer contains styrene structural units and conjugated diene structural units, and the content of the styrene structural units is 15-50 wt% based on the total weight of the copolymer. The content of 1,2-polymerized structural units in the conjugated diene structural units is 8-32%. The randomness of the styrene structural units in the conjugated diene structural units is 30-80%. The degree of hydrogenation of the conjugated diene in the copolymer is 85-100%. This hydrogenated styrene-conjugated diene copolymer has a tear strength of 30-60 MPa, a tear elongation of 300-600%, and a hardness (Shore A) of 70-98. It has a rebound of more than 60% and a compression deformation of less than 30% when foamed using a supercritical carbon dioxide foaming process.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the field of polymer production, and more particularly to a hydrogenated styrene-conjugated diene copolymer, a foamed material produced from the copolymer, and use of the foamed material. [Background technology]

[0002] Hydrogenated styrene-butadiene block polymers (SEBS), hydrogenated styrene-isoprene block polymers (SEPS), and hydrogenated styrene-isoprene and butadiene block polymers (SEEPS) are widely used in various consumer electronics, automobiles, building materials, tools, daily necessities, etc., and their notable features are low modulus, high tensile strength (15-38 MPa), excellent elastic recovery, excellent aging resistance, etc. However, in the application situations that require high tensile and compressive modulus, low hardness and high filling, it is difficult for the conventional hydrogenated styrene-conjugated diene block polymers to meet the requirements of, for example, foamed shoe soles, artificial leather, and electric wires. When producing these products using materials with low tensile modulus, large strain needs to be generated to generate the necessary stress, resulting in insufficient resilience of the sole, and problems such as the surface layer of artificial leather falling off from the cloth layer and the copper wire of the electric wire breaking before the skin layer. Foamed shoe soles made from EVA have problems with compression set and poor anti-slip properties, and making artificial leather from soft PVC or polyurethane has problems with environmental pollution and emitting toxic VOCs during use.

[0003] There are already some shoe factories that use conventional SEBS foaming to manufacture midsoles, and the resilience of the resulting foamed soles is better than EVA (compression ratio is between 30% and 35%, and the upper limit of the resilience rate is 50%), but the drawback is that the melt viscosity of normal SEBS is low, so the cells of the foamed product are not uniform, and some of them burst, resulting in large compression deformation. Also, it is usually necessary to use a chemical foaming method to foam the soles.

[0004] CN102083872B discloses a method for preparing a styrene butadiene copolymer containing styrene monomer microblocks and conjugated diene monomer microblocks by controlling the feeding rate so that the rate at which the monomer is consumed during polymerization is equal to or greater than the rate at which the monomer is added, and controlling the difference between the maximum reaction temperature and the starting temperature not to exceed 50° C. This copolymer needs to be chemically crosslinked and foamed with EVA to obtain a material with higher resilience and lower compression deformation. Summary of the Invention

[0005] An object of the present invention is to provide a hydrogenated styrene-conjugated diene copolymer which can achieve high resilience and low compression deformation without employing a chemical foaming process, a foamed material obtained from said copolymer, and uses of the same.

[0006] A first aspect of the present invention provides a hydrogenated styrene-conjugated diene copolymer, characterized in that it contains a styrene-based structural unit represented by formula 1, a hydrogenated conjugated diene-based structural unit represented by formula 2, and / or a hydrogenated conjugated diene-based structural unit represented by formula 3,

[0007] [ka]

[0008] Here, R1, R2, R3, R4, R5, R6, R7, R8, and R9 are H and C1-C3 alkyl groups, respectively, and R 10is H or a C1-C4 alkyl group, the content of the styrene structural unit is 15 to 50% by weight, preferably 18 to 45% by weight, based on the total amount of the copolymer, the content of the hydrogenated conjugated diene structural unit represented by formula 3 is 8 to 32%, preferably 10 to 30%, more preferably 12 to 25%, based on the total amount of the hydrogenated conjugated diene structural unit represented by formula 2 and the hydrogenated conjugated diene structural unit represented by formula 3, the randomness of the styrene structural unit in the conjugated diene structural unit is 30 to 80%, preferably 35 to 75%, and the hydrogenation degree of the copolymer is 85 to 100%, preferably 95 to 100%.

[0009] A second aspect of the present invention provides a hydrogenated styrene-conjugated diene copolymer foamed material obtained by foaming the above hydrogenated styrene-conjugated diene copolymer.

[0010] A third aspect of the present invention provides a use of the above hydrogenated styrene-conjugated diene copolymer and a foamed material for producing a foamed shoe sole.

[0011] The hydrogenated styrene-conjugated diene copolymer provided by the present invention has a tear strength of 30-60 MPa, a tear elongation of 300-600%, and a hardness (Shore A) of 70-98, and is a high-strength elastomer, with a tensile strength of more than 4 MPa at 10% strain, an elastic recovery of more than 98% at 10% strain, and a tensile strength of more than 8 MPa at 300% strain, and is capable of producing a lightweight foamed material using physical foaming, for example, a carbon dioxide supercritical foaming process. The hydrogenated styrene-conjugated diene copolymer provided by the present invention can be used to obtain a foam with excellent performance, with a resilience of more than 60% and a compression deformation of less than 30%, by employing a carbon dioxide supercritical foaming process. [Brief description of the drawings]

[0012] [Figure 1] FIG. 2 is a TEM (scanning transmission electron microscope) image of the hydrogenated styrene-conjugated diene copolymer provided in Example 1 of the present invention. [Diagram 2]FIG. 1 is a TEM image of a conventional SEBS. [Diagram 3] 1 is a nuclear magnetic resonance hydrogen spectrum of the hydrogenated styrene-conjugated diene copolymer provided in Example 1 of the present invention. [Figure 4] A is the stress-strain curve of the hydrogenated styrene-conjugated diene copolymer provided in Example 1 of the present invention, and B is the stress-strain curve of the commercially available SEBS. [Figure 5A] FIG. 2A is the DSC curve of the hydrogenated styrene-conjugated diene copolymer provided in Example 1 of the present invention; [Figure 5B] B is the DSC curve of the commercially available SEBS. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The endpoints of any ranges and any values ​​disclosed herein are not intended to be limited to the exact ranges or values, but rather should be understood to include any values ​​close to those ranges or values. Numerical ranges can be combined between the endpoints of each range, between the endpoints of each range and any individual point, and between any individual point to obtain one or more new numerical ranges, and these numerical ranges should be considered to be specifically disclosed herein.

[0014] According to the present invention, the styrene-based structural unit represented by formula 1, the hydrogenated conjugated diene-based structural unit represented by formula 2, and the hydrogenated conjugated diene-based structural unit represented by formula 3 are each represented by the following formulas:

[0015] [ka]

[0016] Here, R1, R2, R3, R4, R5, R6, R7, R8, and R9 are each H or an alkyl group of C1 to C3; 10 is H or a C1-C4 alkyl group, where the C1-C4 alkyl group may be, for example, a methyl group, an ethyl group, a propyl group, an isopropyl group, an n-butyl group, an isobutyl group, or a tert-butyl group.

[0017] In the present invention, R 10 are substituents on the benzene ring, which may be one or more, and which are located at the ortho-, meta- or para-position of the vinyl group, preferably at the para-position.

[0018] The styrene-based structural unit is a styrene unit, i.e., R1, R2, and R3 are all H, and R 10 is preferably a methyl group, an ethyl group, a propyl group, an isopropyl group, an n-butyl group, an isobutyl group, or a tert-butyl group. The conjugated diene structural unit is a butadiene structural unit and / or an isoprene structural unit, that is, R4, R5, R6, R7, and R8 are all H, and R9 is H or methyl.

[0019] In order to ensure high resilience and low compression deformation in the copolymer provided by the present invention, the content of styrene-based structural units must not exceed 50% by weight. The present inventors have found that when the content of conjugated diene-based structural units is 50% by weight or more, the hydrogenated copolymer exhibits macroscopically high tensile modulus and tensile strength, and high elastic recovery at low strain, and have found that the reason for this is that the polyethylene chain formed by hydrogenating the polyconjugated diene-based structural units in the molecular chain is divided into multiple polyethylene crystal phases by the polystyrene-based structural units, and the polystyrene-based structural units are pushed out to the surface of the material due to the influence of the crystallization of the polyethylene repeating units, and the cohesive force of the copolymer is improved by the entanglement of the repeating units of the polystyrene structural units. Based on the total amount of the copolymer, the content of styrene-based constituent units is 15 to 50% by weight, and preferably 18 to 45% by weight, and the content of conjugated diene-based constituent units (i.e., the total amount of the hydrogenated conjugated diene-based constituent units represented by formula 2 and the hydrogenated conjugated diene-based constituent units represented by formula 3) is 50 to 85% by weight, and preferably 55 to 82% by weight.

[0020] In order to ensure that the polymer has good tensile modulus and processability, it is necessary to strictly control the content of the hydrogenated conjugated diene structure unit represented by formula 3 (i.e., 1,2 polymerization structure) in the copolymer. The content of the hydrogenated conjugated diene structure unit represented by formula 3 is 8 to 32%, preferably 10 to 30%, and more preferably 12 to 25%, based on the total amount of the hydrogenated conjugated diene structure unit represented by formula 2 (i.e., 1,4 polymerization structure) and the hydrogenated conjugated diene structure unit represented by formula 3. On the other hand, in conventional SEBS, the content of the 1,2 structure is high, usually 35% or more, in order to avoid excessive compression deformation due to crystallization of ethylene.

[0021] In order to ensure that the polyethylene crystal phase in the repeating unit of the conjugated diene structural unit after hydrogenation is uniformly distributed and the polystyrene chains are entangled with each other to form high cohesive force, resulting in high resilience and low compression deformation performance, it is necessary to strictly control the randomness of the styrene structural unit and the hydrogenation degree of the copolymer. Here, the present invention requires that the randomness of the conjugated diene structural unit of the styrene structural unit is 30-80%, preferably 35-75%, and the hydrogenation degree of the copolymer is 85-100%, preferably 95-100%.

[0022] The present invention aims to improve strength and prevent aging by controlling the specific content of conjugated diene 1,2 structure and 1,4 structure, converting the 1,4 structure into a polyethylene structure after hydrogenation, and securing a certain amount of ethylene crystals to form a crystalline phase.

[0023] In the present invention, the content of styrene-based structural units, the content of 1,2 polymerization structural units, and the degree of hydrogenation are all determined by nuclear magnetic resonance hydrogen spectroscopy ( 1 HNMR) method according to the following formula:

[0024] The above substituents R1 to R 10In the copolymer where both are H, δ 6.1-7.2 is assigned to the protons in the benzene ring, δ 4.4-4.9 is assigned to the 1,2 polymerization structure, δ 4.9-5.8 is assigned to the 1,4 polymerization structure, δ 0.4-3.0 is assigned to the alkane region, and δ 4.1-5.9 is assigned to the olefin region.

[0025] 5M1+3M2=A 6.8~7.2 ;

[0026] 2M2=A 6.1~6.8 ;

[0027] 2M3=A 4.4~4.9 ;

[0028] 2M4+M3=A 4.1~5.9 ,

[0029] In the formula, Ax is the spectral peak area corresponding to the x range of δ, M1 is the relative mole fraction of non-block St, M2 is the relative mole fraction of block St, and M3 and M4 are the relative mole fractions of 1,2-polymerized structure and 1,4-polymerized structure of Bd, respectively.

[0030] According to the above assignments, the butadiene content (indicated as Bd) of the whole copolymer is as follows:

[0031] Bd=[A 0.4~3.0 -3(M1+M2)-3M3-4M4] / 8+(M3+M4);(I)

[0032] On the other hand, 1,2 structure content=M3 / Bd;(II)

[0033] The calculation formula for the total hydrogenation degree (H) of the copolymer is as follows:

[0034] H = 1 - (M3 + M4) / {[A 0.4~3.0 -3(M1+M2)-3M3-4M4] / 8+(M3+M4)}. (III)

[0035] For specific methods of obtaining the content of styrene-based structural units, the content of 1,2 polymerization structural units, and the degree of hydrogenation, see Synthetic Rubber Industry, 20120915, 53(5):332-335.

[0036] In the present invention, the substituents R1 to R 10 The degree of randomness in the conjugated diene structural units of the styrene structural units of the copolymer in which each of the units is H is 1 It is measured and calculated by the following formula using a HNMR spectrum chart:

[0037] Randomness = (A 6.8~7.2 -X) / A 6.1~7.2

[0038] A 6.8~7.2 represents the peak area of ​​the three protons at the para and meta positions of the block benzene ring and the five protons of the non-block styrene, and A 6.1~6.8 represents the peak area of ​​the two ortho protons of the block benzene ring, X represents the peak area corresponding to the three protons at the para and meta positions of the block benzene ring, and X / A 6.1~6.8 =3 / 2, A 6.1~7.2 represents the peak area of ​​all protons in the benzene ring in the copolymer.

[0039] According to a preferred embodiment of the present invention, the hydrogenated styrene-conjugated diene copolymer has a crystallization temperature of 18° C. or higher, preferably 18 to 70° C., and an enthalpy of 1.7 J / g or higher, preferably 2.0 to 25.0 J / g, as measured by DSC. DSC was performed using a TA DSCQ10 thermoanalyzer in accordance with a method conforming to GB / T19466.32004, with temperature and enthalpy values ​​calibrated by In and Sn, protected by nitrogen gas, heated from 80° C. to 130° C. at a rate of 10° C. / min, and cooled from 130° C. to 80° C. at a rate of 2° C. / min.

[0040] In order to obtain higher resilience and lower compression deformation, the molecular weight of the hydrogenated styrene-conjugated diene copolymer is preferably 30,000 to 500,000, and more preferably 40,000 to 200,000.

[0041] In the present invention, unless otherwise specified, the molecular weight means a number average molecular weight measured by a gel permeation chromatography (GPC) test method.

[0042] The hydrogenated styrene-conjugated diene copolymer of the present invention preferably has a strength at a predetermined elongation of 300% of 8 MPa or more, and preferably from 10 to 20 MPa, a tear strength of 30 MPa or more, and preferably from 30 to 60 MPa, a tear elongation of 300 to 600%, and preferably from 350 to 500%, a hardness (Shore A) of 80 or more, and preferably from 80 to 98, and a melt index MFR (g / 10 min, 200°C, 5 kg) of 0 to 8, and preferably from 1 to 2.

[0043] In the present invention, the strength, tear strength, tear elongation, and hardness (Shore A) at a specific elongation of 300% are all measured in accordance with GB / T5282009.

[0044] The present inventors have found the following. A TEM image of the copolymer provided by the present invention is shown in Figure 1. The microdomains (white parts in the figure) formed from the styrene-based structural units represented by formula 1 are dispersed in a manner in which columnar distribution, spherical distribution and lamellar distribution coexist in the microdomains (non-white parts in the figure) formed from the hydrogenated conjugated diene-based structural units represented by formula 2 and the hydrogenated conjugated diene-based structural units represented by formula 3, and this phase structure imparts excellent mechanical properties to the polymer.

[0045] Conventional SEBS is a block copolymer in which the ends of each polydiene block (PB) in its phase structure are linked to polystyrene segments (PS), and in the entire system, the polybutadiene segments aggregate to form soft segments, which exhibit the high elasticity of rubber, while the polystyrene segments aggregate to form hard segments, which exhibit the high hardness of plastic. A TEM photograph of this block copolymer is shown in Figure 2. As can be seen from Figure 2, the polystyrene microdomains of conventional SEBS exist only in spherical structures.

[0046] The hydrogenated styrene-conjugated diene random copolymer provided by the present invention can be foamed by a chemical foaming method or a physical foaming method to obtain a foamed material. The physical foaming may be a foaming method using an inert gas such as carbon dioxide or nitrogen gas, and carbon dioxide supercritical foaming, nitrogen gas supercritical foaming, etc. are preferred. The carbon dioxide may be carbon dioxide gas as it is, or may be generated in situ by a chemical method such as carbonate decomposition. Conventional styrene-butadiene copolymers can only be foamed by chemical crosslinking foaming to obtain a foamed material that satisfies the requirements for both resilience and compression deformation.

[0047] The hydrogenated styrene-conjugated diene copolymer provided by the present invention can be obtained by anionic polymerization of styrene and conjugated diene to obtain a base rubber, followed by selective hydrogenation (hydrogenating the double bonds of the conjugated diene units but not hydrogenating the benzene rings) and purification.

[0048] In one embodiment of the present invention, the base rubber synthesis process includes adding a styrene-based monomer represented by the following formula A, a conjugated diene-based monomer represented by the following formula B, a polymerization solvent, a molecular structure modifier, and an alkyl lithium initiator to a polymerization kettle under oxygen-free and anhydrous conditions to randomly copolymerize them to obtain a base rubber.

[0049] [ka]

[0050] Here, R1, R2, R3, R4, R5, R6, R7, R8, R9, R 10 The meaning and selectable range are the same as above.

[0051] According to the present invention, the polymerization reaction can be carried out in various polymerization solvents commonly used in this field, and is not particularly limited, but may be, for example, a hydrocarbon solvent. Usually, the polymerization solvent can be selected from C3 to C20 linear or branched chain or cyclic alkanes, and is preferably selected from C4 to C20 linear or branched chain or cyclic alkanes, and is more preferably at least one selected from n-butane, isobutane, n-pentane, cyclopentane, n-hexane, cyclohexane, n-heptane, n-octane, n-nonane, n-decane, and octane, and is even more preferably one or more selected from cyclopentane, cyclohexane, and n-hexane. The amount of the polymerization solvent used in the present invention is not particularly limited, and may be a conventional selection in this field. In the polymerization system of step (1), the initial total concentration of monomers is preferably 2 to 20% by weight, and more preferably 5 to 16% by weight, depending on the amount of the polymerization solvent used.

[0052] Preferably, the alkyl lithium initiator is at least one of n-butyl lithium, sec-butyl lithium.

[0053] The amount of the alkyllithium initiator used is preferably 0.5 mmol to 3 mmol per 100 g of the polymerizable monomers (the total amount of the styrene-based monomer and the conjugated diene-based monomer).

[0054] In the present invention, the molecular structure modifier is a composite modifier of two or more Lewis bases, and at least one of the molecular structure modifiers is preferably tetrahydrofuran, and tetrahydrofuran preferably accounts for 80% by weight or more of the total amount of the molecular structure modifier, more preferably 95% by weight or more. Other Lewis bases include, for example, tertiary amine compounds and other ether compounds, such as diethyl ether, anisole, dioxane, dimethoxyethane, diethylene glycol dimethyl ether, ethylene glycol dibutyl ether ethyl tetrahydrofurfuryl ether, divinyl ether, ethylene glycol ethyl t-butyl ether, ethylene glycol propyl t-butyl ether, ethylene glycol methyl t-butyl ether, ditetrahydrofuranylpropane, triethylamine, tetramethylethylenediamine, and N-methylmorpholine, and the amount used is 2 to 30 mg / kg, more preferably 5 to 28 mg / kg, based on the weight of the polymerization solvent. The total concentration of the molecular structure modifier in the solvent system is preferably 350 to 650 mg / kg.

[0055] Each of the polymerization monomers may be added all at once, or may be added several times or continuously according to the ratio, as long as the styrene-based monomer and the conjugated diene-based monomer are simultaneously present in the reactor and random copolymerization is carried out.

[0056] In order to ensure high tensile strength of the polymer, it is important to control the randomness of the base rubber. However, since the amount of molecular structure modifier and reaction temperature are important factors for controlling the randomness, the total amount of molecular structure modifier used during the synthesis of the base rubber must be strictly controlled to be between 350 and 650 mg / kg, the amount of THF used is 80% by weight or more, preferably 95% by weight or more of the total amount of molecular structure modifier, and the reaction temperature is controlled to be 55 to 100°C.

[0057] The polymerization reaction time is 45 to 120 minutes, and preferably 60 to 90 minutes.

[0058] After the reaction is completed, the base rubber is added with a co-catalyst and a nickel-based or titanium-based main catalyst, and hydrogenated in the presence of hydrogen to obtain a hydrogenated rubber liquid.

[0059] The base rubber may be selectively hydrogenated by using existing methods to hydrogenate the double bonds of the conjugated diene and not hydrogenate the double bonds in the benzene ring. For example, the hydrogenation method disclosed in CN104945541B may be adopted, the contents of which are also incorporated herein by reference.

[0060] The amount of the cocatalyst used is preferably 8 mg to 129 mg per 100 g of the polymer.

[0061] The amount of the main catalyst used is preferably 17 mg to 200 mg per 100 g of the polymer.

[0062] The amount of the polymer can be calculated from the amount of the monomer charged.

[0063] The co-catalyst is one or more selected from alcohols and esters, preferably one or more selected from monohydric alcohols, polyhydric alcohols, linear alkyl ester compounds, benzoic acid ester compounds, phthalic acid ester compounds, and paraoxybenzoic acid ester compounds, more preferably one or more selected from C1 to C10 monohydric alcohols, C2 to C10 polyhydric alcohols, C2 to C10 linear alkyl ester compounds, C7 to C15 benzoic acid ester compounds, C7 to C15 phthalic acid ester compounds, and C7 to C15 paraoxybenzoic acid ester compounds, and most preferably one or more selected from methanol, isooctanol, methyl benzoate, dimethyl phthalate, and dibutyl phthalate.

[0064] Preferably, after the reaction of the hydrogenated rubber liquid with soft water is completed, the hydrogenated rubber liquid is purified, the metal ion impurities in the hydrogenated rubber liquid are removed, the hydrogenated rubber liquid is coagulated with steam, and then dried and pulverized to obtain the above hydrogenated styrene-conjugated diene random copolymer. The metal ion impurities in the hydrogenated rubber liquid can be removed by oxidation with decanoic acid, emulsification extraction with soft water, centrifugation, and settling to separate the aqueous phase. For example, the method described in CN201410063616.3 can be referred to to remove the metal ions in the polymer, the rubber liquid after removal is coagulated with steam, the solvent is recovered and recycled, and the polymer particles are dried and pulverized to obtain the finished product.

[0065] Preferably, the oxidation conditions for t-decanoic acid are such that the amount of t-decanoic acid used is 0.5 ml to 1 ml per 100 g of polymer, and the oxidation time is 15 to 25 minutes.

[0066] As the conditions for soft water emulsification extraction, the amount of soft water used is preferably 50 to 100 ml per 100 g of polymer, and the emulsification time is preferably 15 to 25 minutes.

[0067] The conditions for the steam aggregation are preferably such that steam at 110 to 130° C. is passed through a 10 L aggregation vessel and the aggregation time is 20 to 40 minutes.

[0068] As drying conditions, it is preferable that the temperature of the air blower oven is 80 to 120° C. and the drying time is 1 to 4 hours.

[0069] The present invention further provides a hydrogenated styrene-conjugated diene random copolymer foam material, which is obtained from the hydrogenated styrene-conjugated diene random copolymer by carbon dioxide supercritical foaming.

[0070] The present inventors have obtained a hydrogenated styrene-conjugated diene copolymer having a density of 0.1 to 0.9 g / cm by carbon dioxide supercritical foaming from the hydrogenated styrene-conjugated diene copolymer provided above. 3It has been newly discovered that a material can be obtained whose hardness (Shore C) can be adjusted in the range of 5 to 85, and that this material also has the characteristics of high resilience, high impact absorption, low compression set, high slip resistance, yellowing resistance, and VOC-free. The material obtained by carbon dioxide supercritical foaming of the above hydrogenated styrene-conjugated diene random copolymer provided by the present invention has a resilience of 58 to 65% as measured in accordance with ASTM D2632, and a compression deformation of 20 to 28% as measured in accordance with GB / T66692008.

[0071] The inventors of the present invention have found that using the hydrogenated styrene-conjugated diene copolymer together with at least one of white oil, polyolefin, inorganic filler, SEBS (hydrogenated styrene butadiene block copolymer) and SEPS (hydrogenated styrene isoprene block copolymer) as a compounding material and utilizing carbon dioxide supercritical foaming together contributes to further improving the performance of the foam material.

[0072] Here, the weight ratio of the hydrogenated styrene-conjugated diene copolymer to the blending material may be 5-10:1.

[0073] The conditions for the carbon dioxide supercritical foaming include a foaming pressure of, for example, 10 to 30 MPa and a foaming temperature of, for example, 110 to 140°C.

[0074] The foam material may be a wire, a shaped material, a sheet material, or the like.

[0075] The present invention further provides use of the above-mentioned hydrogenated styrene-conjugated diene copolymer foamed material in the production of foamed shoe soles, etc.

[0076] The foamed shoe sole manufactured from the material obtained by foaming the hydrogenated styrene-conjugated diene copolymer provided by the present invention has the characteristics of high resilience and low compression deformation, which is advantageous in that it has high resilience and low compression deformation compared to foamed shoe soles manufactured from conventional SEBS or EVA foam materials.

[0077] The following examples further illustrate the present invention but are not intended to limit it.

[0078] In the following examples, the molecular weight and distribution of polymers were measured by gel permeation chromatography. The instrument used was a Japan Shimadzu LCD-10ADvp gel permeation chromatography, the detector was a RID-10A differential refractometer, the separation column was GPC804, 805, the flow rate of the mobile phase THF was 1 mL / min, the measurement temperature was room temperature, the calibration was performed with monodisperse polystyrene, and the data processing was performed with a Shimadzu CR-7A.

[0079] The styrene unit content, 1,2 structure content, hydrogenation degree and randomness were all calculated from the nuclear magnetic resonance hydrogen spectrum. The instrument used was a Bruker AV400 spectrometer (400 MHz), and the measurement was performed at room temperature using CDCl3 as the solvent.

[0080] Polymer mechanical properties (strength, tear strength, tear elongation, etc. at a specified elongation of 300%) are measured according to GB / T528-2009 method.

[0081] The melt index (MFR) is measured according to the GB / T3682.12018 method (200°C, 5 kg).

[0082] The DSC chart was measured using a TA DSCQ10 thermoanalyzer in accordance with GB / T19466.32004, with temperature and enthalpy values ​​calibrated by In and Sn, protected by nitrogen gas, heated from 80°C to 130°C at a rate of 10°C / min, and cooled from 130°C to 80°C at a rate of 2°C / min.

[0083] The rebound of the foam material is measured according to ASTM D2632, the compression deformation is measured according to GB / T 66692008, the dry friction coefficient and the wet friction coefficient are measured according to ASTM F609 method, the density is measured by GB / T 63432009 method, and the oxidation induction period (OIT) is measured according to GB / T 2951.91997.

[0084] Example 1 The base rubber (mass ratio of base rubber S / B is 35 / 65) is synthesized by anionic polymerization, and then selectively hydrogenated using a titanium-based catalyst. The process includes the following steps:

[0085] Step (1a): Synthesis of base rubber Into a 5L polymerization kettle purged with high-purity nitrogen gas, 3000mL of pure cyclohexane (water content <20mg / kg), tetrahydrofuran in an amount equivalent to 350mg / kg of solvent, and 5mg / kg of ethyl tetrahydrofurfuryl ether were added, stirring was started, the temperature was raised to 60°C, 6.0mmol of n-butyllithium was added, and then a mixed monomer of 195g of butadiene and 105g of styrene was added. The mixed monomer was added to the polymerization kettle in a lump-sum manner so as to control the reaction temperature to 100°C or less, and the reaction was continued for another 50 minutes at 70°C to obtain a polymerized rubber liquid.

[0086] Step (1b): Hydrogenation of base rubber The polymerized rubber liquid was placed in a 5 L hydrogenation kettle and heated to 70°C. 4 mL (0.2 mol / L) of dibutyl phthalate as a co-catalyst and 0.2 g of dicyclopentadiene titanium dichloride as a main catalyst were added, hydrogen gas was passed through the liquid, and the hydrogenation pressure was controlled to 1.5 MPa, and the hydrogenation reaction was carried out for 2 hours.

[0087] Step (1c): Purification of rubber liquid After the hydrogenation reaction was completed, the hydrogenated rubber liquid was transferred to a water washing vessel and heated to 60-65℃. The metallic lithium in the rubber liquid was removed by washing with t-decanoic acid, and then the mixture was emulsified and extracted with 300mL of soft water for 15 minutes, centrifuged, and allowed to stand to separate the aqueous phase. The remaining rubber liquid was coagulated with steam and dried to obtain a hydrogenated styrene-butadiene copolymer. The properties of the copolymer are shown in Table 1.

[0088] The TEM image of the obtained hydrogenated styrene-butadiene copolymer is shown in Figure 1. As can be seen from Figure 1, layered and columnar / globular structures exist simultaneously in the TEM image of this hydrogenated styrene-butadiene copolymer.

[0089] The nuclear magnetic resonance hydrogen spectrum of the obtained hydrogenated styrene-butadiene copolymer is shown in Figure 3. From Figure 3, the hydrogenation structure and microstructure can be observed, and the calculation results of the degree of hydrogenation and the degree of randomness are shown in Table 1.

[0090] The stress-strain curve of the obtained hydrogenated styrene-butadiene copolymer is shown in Figure 4A. As is clear from Figure 4, the hydrogenated copolymer provided by the present invention has a tensile strength of 41 MPa or more and a strength at a given elongation of 300% of 11 MPa or more, and thus has a high tensile modulus and strength at a given elongation of 300%.

[0091] The DSC chart of the obtained hydrogenated styrene-butadiene copolymer is shown in Figure 5A. As is clear from Figure 5, the hydrogenated copolymer of the present invention has a crystallization temperature of about 55°C and an enthalpy value of about 20 J / g.

[0092] Example 2 The polymer was synthesized according to the method of Example 1. The difference is that the base rubber with an S / B mass ratio of 30 / 70 was synthesized by anionic polymerization. The specific synthesis procedure of the base rubber is as follows:

[0093] In a 5L polymerization kettle purged with high-purity nitrogen gas, 3000mL of pure cyclohexane (water amount <20mg / kg), tetrahydrofuran in an amount equivalent to 450mg / kg of solvent, and 10mg / kg of tetramethylethylenediamine were added, stirring was started, the temperature was raised to 60°C, 6.0mmol of n-butyllithium was added, and then a mixed monomer of 210g of butadiene and 90g of styrene was added, and the mixed monomer was added to the polymerization kettle in a batch-feed manner so as to control the reaction temperature below 100°C, and the reaction was continued for 55 minutes at 70°C. The rubber liquid was hydrogenated and purified in the manner of Example 1, and the properties of the copolymer are shown in Table 1. The TEM diagram is similar to that of Example 1.

[0094] Example 3 The polymer was synthesized according to the method of Example 1. The difference is that the base rubber with an S / B mass ratio of 20 / 80 was synthesized by anionic polymerization. The specific synthesis procedure of the base rubber is as follows:

[0095] In a 5L polymerization kettle purged with high purity nitrogen gas, 3000mL of pure cyclohexane (water amount <20mg / kg), tetrahydrofuran in an amount equivalent to 550mg / kg of solvent, and 15mg / kg of ditetrahydrofuranylpropane were charged, stirring was started, the temperature was raised to 60°C, 6.0mmol of n-butyllithium was added, and then a mixed monomer of 240g of butadiene and 60g of styrene was added, and the mixed monomer was added to the polymerization kettle in a batch-feed manner so as to control the reaction temperature to 100°C or less, and the reaction was continued for 55 minutes at 70°C. The rubber liquid was hydrogenated and purified according to the method of Example 1 to obtain a copolymer, and the properties of the copolymer are shown in Table 1. The TEM image is similar to that of Example 1.

[0096] Example 4 The polymer was synthesized according to the method of Example 1. The difference is that the base rubber with an S / B mass ratio of 45 / 55 was synthesized by anionic polymerization. The specific synthesis procedure of the base rubber is as follows:

[0097] In a 5L polymerization kettle purged with high-purity nitrogen gas, 3000mL of pure cyclohexane (water amount <20mg / kg), tetrahydrofuran in an amount equivalent to 500mg / kg of solvent, and 12mg / kg of ethyl tetrahydrofurfuryl ether were added, stirring was started, the temperature was raised to 60°C, 6.0mmol of n-butyllithium was added, and then a mixed monomer of 165g of butadiene and 135g of styrene was added, and the mixed monomer was added to the polymerization kettle in a batch-feed manner so as to control the reaction temperature to 100°C or less, and the reaction was continued for 55 minutes at 70°C. The rubber liquid was hydrogenated and purified according to the method of Example 1 to obtain a copolymer, and the properties of the copolymer are shown in Table 1. The TEM image is similar to that of Example 1.

[0098] Example 5 The base rubber (mass ratio of base rubber S / B is 38 / 62) is synthesized by anionic polymerization, and then selectively hydrogenated using a titanium-based catalyst. The process includes the following steps:

[0099] Step (1a): Synthesis of base rubber Into a 5L polymerization kettle purged with high purity nitrogen gas, 3000mL of pure cyclohexane (water amount <20mg / kg), tetrahydrofuran in an amount equivalent to 550mg / kg of solvent, and 25mg / kg of ethyl tetrahydrofurfuryl ether were added, stirring was started, the temperature was raised to 60°C, 10.0mmol of n-butyllithium was added, and then a mixed monomer of 186g of butadiene and 114g of styrene was added. The mixed monomer was added to the polymerization kettle in a lump-sum manner so as to control the reaction temperature to 100°C or less, and the reaction was continued for 55 minutes at 70°C to obtain a polymerized rubber liquid.

[0100] Step (1b): Hydrogenation of base rubber This is the same as in Example 1.

[0101] Step (1c): Purification of rubber liquid The procedure was the same as in Example 1. The hydrogenated styrene-butadiene copolymer was obtained, and its properties are shown in Table 1.

[0102] Example 6 The difference is that the polymer was synthesized according to the method of Example 1, and the base rubber with an S / B mass ratio of 25 / 75 was synthesized by anionic polymerization. The specific synthesis procedure of the base rubber is as follows:

[0103] In a 5L polymerization kettle substituted with high purity nitrogen gas, 3000mL of pure cyclohexane (water amount <20mg / kg), tetrahydrofuran in an amount equivalent to 580mg / kg of solvent, and 20mg / kg of ditetrahydrofuranylpropane were charged, stirring was started, the temperature was raised to 60°C, 6.0mmol of n-butyllithium was added, and then a mixed monomer of 225g of butadiene and 75g of styrene was added, and the mixed monomer was added to the polymerization kettle in a batch-feed manner so as to control the reaction temperature to 100°C or less, and the reaction was continued for 55 minutes at 70°C. The rubber liquid was hydrogenated and purified according to the method of Example 1 to obtain a copolymer, and the properties of the copolymer are shown in Table 1. The TEM image is similar to that of Example 1.

[0104] Example 7 The polymer was synthesized according to the method of Example 1. The difference is that the base rubber with an S / B mass ratio of 32 / 68 was synthesized by anionic polymerization. The specific synthesis procedure of the base rubber is as follows:

[0105] In a 5L polymerization kettle purged with high-purity nitrogen gas, 3000mL of pure cyclohexane (water amount <20mg / kg), tetrahydrofuran in an amount equivalent to 580mg / kg of solvent, and 25mg / kg of ditetrahydrofuranylpropane were charged, stirring was started, the temperature was raised to 60°C, 4.0mmol of n-butyllithium was added, and then a mixed monomer of 204g of butadiene and 96g of styrene was added, and the mixed monomer was added to the polymerization kettle in a batch-feed manner so as to control the reaction temperature to 100°C or less, and the reaction was continued for 55 minutes at 70°C. The rubber liquid was hydrogenated and purified according to the method of Example 1 to obtain a copolymer, and the properties of the copolymer are shown in Table 1. The TEM image is similar to that of Example 1.

[0106] Comparative Example 1 The preparation of styrene-butadiene copolymer was carried out according to the method of Example 2 of CN102083872B.

[0107] Comparative Example 2 A styrene-butadiene copolymer was prepared according to the method of Example 2 of CN102083872B, and the copolymer was hydrogenated and purified according to steps (1b) and (1c) of Example 1 of the present invention.

[0108] Comparative Example 3 The difference is that a hydrogenated styrene-butadiene copolymer was produced according to the method of Example 2, and a base rubber with an S / B mass ratio of 60 / 40 was synthesized.

[0109] Comparative Example 4 A conventional SEBS product (a hydrogenated styrene butadiene styrene triblock copolymer, with an S / B weight ratio of 33 / 67, a 1.2 polymer structure content of 36.5-37.5%, and a number average molecular weight of 198,000). Its TEM photograph is shown in FIG. 2. As is clear from FIG. 2, only spherical structures are present. Its stress-strain curve is as shown in FIG. 4B. As is clear from FIG. 4, the tensile strength of the commercial SEBS is about 20 MPa, which is much smaller than the tensile strength of the copolymer of the present invention. Its DSC curve is as shown in FIG. 5B. As is clear from FIG. 5, the crystallization temperature of this commercial SEBS is about 16° C., and the enthalpy value is 2.6 J / g.

[0110] Comparative Example 5 The base rubber (mass ratio of base rubber S / B is 38 / 62) is synthesized by anionic polymerization, and then selectively hydrogenated using a titanium-based catalyst. The process includes the following steps:

[0111] Step (1a): Synthesis of base rubber Into a 5L polymerization kettle purged with high purity nitrogen gas, 3000mL of pure cyclohexane (water content <20mg / kg) and ditetrahydrofuranylpropane in an amount equivalent to 250mg / kg of solvent were charged, stirring was started, the temperature was raised to 60°C, 8.0mmol of n-butyllithium was added, and then a mixed monomer of 186g of butadiene and 114g of styrene was added. The mixed monomer was added to the polymerization kettle in a batch-feed manner so as to control the reaction temperature to 100°C or less, and the reaction was continued for another 60 minutes at 80°C to obtain a polymerized rubber liquid.

[0112] Step (1b): Hydrogenation of base rubber This is the same as in Example 1.

[0113] Step (1c): Purification of rubber liquid The procedure was the same as in Example 1. The hydrogenated styrene-butadiene copolymer was obtained, and its properties are shown in Table 1.

[0114] Comparative Example 6 The base rubber (mass ratio of base rubber S / B is 38 / 62) is synthesized by anionic polymerization, and then selectively hydrogenated using a titanium-based catalyst. The process includes the following steps:

[0115] Step (1a): Synthesis of base rubber This is the same as in Example 1.

[0116] Step (1b): Hydrogenation of base rubber The polymerized rubber liquid was placed in a 5 L hydrogenation kettle and heated to 70°C. 4 mL (0.1 mol / L) of dibutyl phthalate as a co-catalyst and 0.1 g of dicyclopentadiene titanium dichloride as a main catalyst were added, hydrogen gas was passed through the liquid, and the hydrogenation pressure was controlled to 1.0 MPa to carry out the hydrogenation reaction for 1 hour.

[0117] Step (1c): Purification of rubber liquid The procedure was the same as in Example 1. The hydrogenated styrene-butadiene copolymer was obtained, and its properties were as shown in Table 1.

[0118] Comparative Example 7 The base rubber (mass ratio of base rubber S / B is 30 / 70) is synthesized by anionic polymerization, and then selectively hydrogenated using a titanium-based catalyst. Specifically, the process includes the following steps:

[0119] Step (1a): Synthesis of base rubber Into a 5 L polymerization kettle replaced with high purity nitrogen gas, 3000 mL of pure cyclohexane (water content <20 mg / kg) and tetrahydrofuran in an amount equivalent to 200 mg / kg of solvent were added, stirring was started, the temperature was raised to 70°C, 8.0 mmol of n-butyllithium was added, and then a mixed monomer of 210 g of butadiene and 90 g of styrene was added. The mixed monomer was added to the polymerization kettle in a lump-sum charging method so as to control the reaction temperature to 100°C or less, and the reaction was continued for 60 minutes at 80°C to obtain a polymerized rubber liquid.

[0120] Step (1b): Hydrogenation of base rubber This is the same as in Example 1.

[0121] Step (1c): Purification of rubber liquid The procedure was the same as in Example 1. The hydrogenated styrene-butadiene copolymer was obtained, and its properties were as shown in Table 1.

[0122] The performance measurement results of the synthetic samples of Examples 1 to 7 and Comparative Examples 1 to 7 are shown in Table 1 below.

[0123] [Table 1-1]

[0124] [Table 1-2]

[0125] Note: "None" for crystallization temperature and enthalpy indicates that no crystallization peak is observed in the DSC curve, "None" for TEM characteristics indicates that no layered, columnar or spherical structure is observed in the TEM, and "Not measurable" indicates that the polymer is too soft to measure the data by Shore A hardness tester.

[0126] From the results in Table 1 above, it can be seen that the copolymer provided by the present invention has good mechanical properties and antioxidation performance.

[0127] Performance Testing 1) The copolymers obtained in the above Examples 1 to 7 and Comparative Examples 1 to 7 were mixed and granulated in an extruder, and the granulation temperature (nose temperature) was set to 200°C as the granulation condition. Then, the hydrogenated styrene-butadiene copolymer particles (particle size 0.5 to 1 cm) were immersed in carbon dioxide supercritical fluid, and the supercritical fluid was allowed to reach dissolution equilibrium in the hydrogenated styrene-butadiene copolymer particle substrate. The hydrogenated styrene-butadiene copolymer particles were then placed in a high-pressure reactor and heated to foam, and the foaming conditions included a foaming pressure of 20 MPa and a foaming temperature of 120°C, to obtain hydrogenated styrene-butadiene copolymer foamed particles. The foamed particles were press-formed into foamed boards (approximately 1 cm thick) using a mold, and the performance test results of the foamed boards are shown in Table 2 below.

[0128] 2) The copolymers obtained in Examples 1-4 and Comparative Examples 1-3 were mixed with white oil (26#, Shandong Lifeng Chemical New Materials Co., Ltd.), polypropylene (Yanshan Petrochemical K8303), CaCO3, SEBS (Baling Petrochemical YH503) or SEPS (Baling Petrochemical YH4053), and the recipe is shown in Table 3. The mixture was foamed with CO2 supercritical foaming, and the foaming conditions included a foaming pressure of 20 MPa and a foaming temperature of 120°C, to obtain hydrogenated styrene-butadiene copolymer foam particles. The foam particles were pressed into a foam board (about 1 cm thick) using a mold, and the performance test results of the foam board are shown in Table 4 below.

[0129] [Table 2-1]

[0130] [Table 2-2]

[0131] [Table 3]

[0132] [Table 4]

[0133] As is clear from the results in Table 2, the present invention makes it possible to obtain a foamed material having high resilience and low compression deformation by controlling the specific styrene content, the specific 1,2 structure content, and the specific hydrogenation degree and randomness of the hydrogenated copolymer, and then foaming the obtained copolymer with carbon dioxide.

[0134] From the results in Tables 2 and 4, it can be seen that the foam density and hardness of the formulated rubber using the hydrogenated copolymer of the present invention are improved by adding a filler, but the resilience and compression deformation performance of the foam are still good.

Claims

1. A hydrogenated styrene-conjugated diene copolymer containing a styrene-based structural unit represented by formula 1, a conjugated diene-based structural unit represented by formula 2, and a conjugated diene-based structural unit represented by formula 3, 【Chemistry 1】 In formula 1, R 1 , R 2 , R 3 are each H or a C1-C3 alkyl group, R 10 is H or a C1-C4 alkyl group, and in formula 2, R 4 , R 5 , R 6 , R 7 , R 8 , R 9 are each H or a C1-C3 alkyl group, and in formula 3, R 4 , R 5 , R 6 , R 7 , R 8 , R 9 are each H or a C1-C3 alkyl group, A hydrogenated styrene-conjugated diene copolymer, characterized in that the content of styrene-based structural units is 18 to 50 wt % based on the total amount of the copolymer, the content of hydrogenated conjugated diene-based structural units represented by formula 3 is 8% or more and less than 25% based on the total amount of the hydrogenated conjugated diene-based structural units represented by formula 2 and the hydrogenated conjugated diene-based structural units represented by formula 3, the randomness of the styrene-based structural units in the conjugated diene-based structural units is 30 to 80%, and the hydrogenation degree of the conjugated diene in the copolymer is 85 to 100%.

2. 2. The hydrogenated styrene-conjugated diene copolymer according to claim 1, wherein the content of the styrene-based structural unit is 18 to 45 wt % based on the total amount of the copolymer.

3. The hydrogenated styrene-conjugated diene copolymer according to claim 1, wherein the content of the styrene structural unit is 25 to 35 wt % based on the total amount of the copolymer, the content of the hydrogenated conjugated diene structural unit represented by formula 3 is 10% or more and less than 25% based on the total amount of the hydrogenated conjugated diene structural unit represented by formula 2 and the hydrogenated conjugated diene structural unit represented by formula 3, the randomness of the styrene structural unit in the conjugated diene structural unit is 35 to 70%, and the hydrogenation degree of the conjugated diene in the copolymer is 95 to 100%.

4. 3. The hydrogenated styrene-conjugated diene copolymer according to claim 1 or 2, which has a crystallization temperature of 18° C. or higher and an enthalpy of 1.7 J / g or higher as measured by DSC.

5. The hydrogenated styrene-conjugated diene copolymer according to claim 4, wherein the hydrogenated styrene-conjugated diene copolymer has a crystallization temperature of 18 to 70° C. and an enthalpy of 2 to 25 J / g as measured by DSC.

6. The hydrogenated styrene-conjugated diene copolymer according to any one of claims 1 to 5, wherein the microdomains formed from the styrene-based structural unit represented by formula 1, the microdomains formed from the hydrogenated conjugated diene-based structural unit represented by formula 2 and the hydrogenated conjugated diene-based structural unit represented by formula 3, and the microdomains exhibit a coexistence state of a columnar or spherical structure and a layer structure.

7. The hydrogenated styrene-conjugated diene copolymer according to any one of claims 1 to 6, wherein the styrene-based structural unit represented by formula 1, the hydrogenated conjugated diene-based structural unit represented by formula 2, and the hydrogenated conjugated diene-based structural unit represented by formula 3 are respectively represented by the following formulas 1-1, 2-1, and 3-1. 【Chemistry 2】

8. 8. The hydrogenated styrene-conjugated diene copolymer according to claim 1, wherein the number average molecular weight of the copolymer measured by gel permeation chromatography is from 30,000 to 500,000.

9. 9. The hydrogenated styrene-conjugated diene copolymer according to claim 8, wherein the number average molecular weight of the copolymer measured by gel permeation chromatography is from 40,000 to 200,000.

10. 10. The hydrogenated styrene-conjugated diene copolymer according to claim 9, wherein the number average molecular weight of the copolymer measured by gel permeation chromatography is from 50,000 to 80,000.

11. The hydrogenated styrene-conjugated diene copolymer according to any one of claims 1 to 10, wherein the copolymer has a strength at a predetermined 300% elongation of 8 MPa or more, a tear strength of 30 MPa or more, a tensile elongation of 300 to 600%, a hardness (Shore A) of 80 or more, and a melt index (200°C, 5 kg) of 0 to 8 g / 10 min.

12. The hydrogenated styrene-conjugated diene copolymer according to claim 11, wherein the copolymer has a strength at a predetermined 300% elongation of 10 to 20 MPa, a tear strength of 30 to 60 MPa, a tensile elongation of 350 to 500%, a hardness (Shore A) of 80 to 98, and a melt index (200°C, 5 kg) of 1 to 2 g / 10 min.

13. Use of the hydrogenated styrene-conjugated diene copolymer according to any one of claims 1 to 12 in the production of a foamed shoe sole.

Citation Information

Patent Citations

  • Crosslinked rubber composition

    JP1992139219A

  • Rubber composition for shape

    JP1994299001A

  • Crosslinked rubber, member for tires, vibration-proofing member, member for belts, and rubber composition

    WO2015064646A1